Sports Culture in Latin American History - Sheinin, David (Book collections on Project MUSE., 2015)
Perhaps no other activity is more synonymous with passion, identity, bodily ideals, and the power of place than sport. As the essays in this volume show, the function of sport as a historical and cultural marker is particularly relevant in Latin America. From the late nineteenth century to the present, the contributors reveal how sport opens a wide window into local, regional, and national histories. The essays examine the role of sport as a political vehicle, in claims to citizenship, as a source of community and ethnic pride, as a symbol of masculinity or feminism, as allegorical performance, and in many other purposes. Sports Culture in Latin American History juxtaposes analyses of better-known activities such as boxing and soccer with first peoples' athletics in Argentina, Cholita wrestling in Bolivia, the African-influenced martial art of capoeira, Japanese Brazilian gateball, the "Art Deco" body ideal for postrevolutionary Mexican women, Jewish soccer fans in Argentina and transgressive behavior at matches, and other topics. The contributors view the local origins and adaptations of these athletic activities and their significance as insightful narrators of history and culture.